2003
DOI: 10.1034/j.1399-0004.2003.00049.x
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of clinical variability in familial deletion 22q11.2: from full manifestation to extremely mild clinical anomalies

Abstract: The 22q11.2 deletion (del22q11.2) syndrome is a genetic condition with wide interfamilial and intrafamilial variability in clinical expression. The aim of the present study was to review the prevalence of parental transmission in our series of patients with del22q11.2, and to analyse clinical findings of the affected parents. Parental transmission of del22q11.2 in our series was 17.2% (15/87), with a preferential maternal transmission (10/15). One or more major features of del22q11.2 were found in all deleted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
89
0
8

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(105 citation statements)
references
References 35 publications
7
89
0
8
Order By: Relevance
“…48 The most common features include cardiovascular anomalies, palate anomalies, feeding disorders, speech and learning disabilities, renal anomalies, and behavioral disorders. Other abnormalities may include hypocalcemia, immunodeficiency, skeletal abnormalities, and growth hormone deficiency.…”
Section: Loci and Genes Associated With Congenital Heart Defects Idenmentioning
confidence: 99%
“…48 The most common features include cardiovascular anomalies, palate anomalies, feeding disorders, speech and learning disabilities, renal anomalies, and behavioral disorders. Other abnormalities may include hypocalcemia, immunodeficiency, skeletal abnormalities, and growth hormone deficiency.…”
Section: Loci and Genes Associated With Congenital Heart Defects Idenmentioning
confidence: 99%
“…These include the hemizygosity of the 45 genes in the 22q11.2 deletion region and interaction of the effects of hemizygosity with genetic variants both in the intact chromosome 22 and elsewhere in the genome. 8,9 In families of probands with 22q11.2 deletions, an elevated prevalence of CHD in relatives without 22q11.2 deletions would support this hypothesis of genetic interaction. Two previous pediatric studies have suggested such an elevated prevalence of CHD.…”
mentioning
confidence: 57%
“…Shprintzen after 30 years of study of the anomaly wrote that del22 syndrome has a wide spectrum of phenotypes with more than 180 clinical manifestations that involve essentially every organ (3), and also found that different dysmorphic features can be seen in different racial groups and different ages (4) and even in one and the same family (2,4). In this way, the spectrum of associated involvements becomes wider (5). According to Marino et al, cardiovascular malformations are always present in these patients (6).…”
mentioning
confidence: 99%